Triple differential cross-section formulation for two-electron photoionization of the helium metastable (1s2s) 1,3 S states - M. Arifin (Indonesian Journal of Physics, 2003)
The triple differential cross-section (TDCS) for two-electron photoionization on the helium metastable (1s2s)1,3S states has been formulated. The momentum space formulation of the close-coupling theory was employed to describe nonperturbatively the inelastic scattering in the final state of the atom. To represent the electron-electron correlation in the initial states the multiconfiguration Hartree-Fock method was used. A Laguerre basis (L2) was chosen to expand the target spaces both in the discrete and continuum states. The TDCS as well as the single and double photoionization cross-sections were obtained directly by solving the Lippmann-Schwinger integral equations.